Peran Gerakan Literasi Dan Minat Baca Dalam Membentuk Karakter Religius Siswa MTsN 5 Jombang - Anik Zuroidah; Muhtadi; Abdul Rouf (Arsy : Jurnal Studi Islam, 2019)
Literacy becomes the hot topic spoken among practitioners especially in education environment. However, many people do not know what activities are included in it. An online information mentions that literacy is intended to carry out the habit of thinking followed by the process of reading and writing, which in turn can create a work. In Islam, the basis of this literacy activity is very strong. This can be seen in the Qur'an surah Al Alaq verse 1, which means: "Let's read (in the name of your Lord who created). From this statement we know that to gain skills in life requires the ability to process the knowledge gained. Based on the above background, the problems to be discussed in this study are (1) How is the literacy movement in MTsN 5 Jombang? (2) How is the reading interest of MTsN 5 Jombang students? (3) How is the religious character of MTsN 5 Jombang students? and (4) What is the influence of the Literacy Movement and reading interest on the religious character of MTsN 5 Jombang students? From the formulation of the problem, it was found that the literacy movement in MTSN 5 Jombang was in accordance with the guidance of the madrasah literacy movement. This can be proven by the activities of students who have carried out the literacy movement stages starting from the stage of habituation, development, and learning. The reading interest of MTsN 5 Jombang students was initially low. With various efforts gradually the students' interest in reading began to grow. The religious character of MTsN 5 Jombang students varies greatly. This relates to the diverse backgrounds of students. The role of literacy and reading interest is very important in shaping the religious character of MTsN 5 Jombang students. The change in religious behavior that appears is positive behavior in its relationship with God, others, and the environment. Those who were not aware in praying became diligent in their prayers, who were less diligent became disciplined. Who originally unpolite with parents, become obedient to parents. Who was originally ignorant to friends, became friends. Those who used to say dirty, turned polite. Those who used to be prejudiced were not good, now they like being kind. Those who used to lie, changed easily to admit mistakes. Likewise with the role of students' interest in reading. Reading interest that grows from literacy movement activities enables students to absorb information from reading material and then make it a student who has a religious character.